From health tips to tech hacks, find it all on IDNLearn.com. Ask anything and receive comprehensive, well-informed responses from our dedicated team of experts.
Sagot :
Answer:
20
Step-by-step explanation:
3 (b + a) = c
3 (4 + 5) = 7
12 + 15 = 7
27 = 7
27 - 7
20
[tex]\huge\boxed{ \sf{Answer}} [/tex]
Given,
[tex]a = 5 \\ b = 4 \\ c = 7[/tex]
And the equation we need to solve is,
[tex]3(b + a) = c[/tex]
To find the answer, you need to substitute the values of a, b & c in the equation.
[tex]3(b + a) = c \\ 3b + 3a = c \\ ( 3 \times 4) +( 3 \times 5) = 7 \\ 12 + 15 = 7 \\ 12 + 15 - 7 = 0 \\ = 27 - 7 \\ = 20[/tex]
↦ The answer is 20.
ʰᵒᵖᵉ ⁱᵗ ʰᵉˡᵖˢ
꧁❣ ʀᴀɪɴʙᴏᴡˢᵃˡᵗ2²2² ࿐
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Thank you for choosing IDNLearn.com. We’re committed to providing accurate answers, so visit us again soon.